Self‐Adhesive Silicone Microstructures for the Treatment of Tympanic Membrane Perforations. Issue 10 (31st July 2021) - Moreira Lana, Gabriela; Sorg, Katharina; Wenzel, Gentiana Ioana; Hecker, Dietmar; Hensel, René; Schick, Bernhard; Kruttwig, Klaus; Arzt, Eduard
Abstract : Inspired by the gecko foot, polymeric microstructures have demonstrated reliable dry adhesion to both stiff objects and sensitive surfaces such as skin. Microstructured silicone patches are proposed, herein, for the treatment of tympanic membrane perforations with the aim of serving as an alternative for current surgical procedures that require anesthesia and ear canal packing. Sylgard 184 PDMS micropillars of 20 μm in diameter and 60 μm in length are topped by a Soft Skin Adhesive (SSA) MG7‐1010 terminal layer, of about 25 μm thickness. The adhesion is evaluated by specially designed tack tests against explanted murine eardrums and, for comparison, against a rigid substrate. Functional effects are evaluated using auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAE). The adhesion strength of the microstructure and unstructured controls to explanted murine tympanic membranes is comparable (typically 12 kPa), but the microstructured patches are easier to handle by the surgeon. For the first time, partial recovery of hearing performance is measured immediately after patch application. The novel patches adhere without the need for further fixation, removing the need for ear canal packing. The proposed material design holds great promise for improving clinical treatments of tympanic membrane perforations. Abstract : Silicone microstructures are proposed as a bioinspired nonchemical adhesive for repair of tympanic membranes. Micropillars with diameter of 20 μm topped by a soft adhesive layer achieve reliable adhesion to skin and simplify the surgical handling of the patch. Mouse experiments confirm the adhesive performance to the eardrum and demonstrate partial recovery of hearing immediately after patch application.